Purification of thymus mRNA coding for a 16,000-dalton polypeptide containing the thymosin alpha 1 sequence. - Freire, M (1981)
A mRNA fraction purified by preparative polyacrylamide disc gel electrophoresis from calf thymus polysomes codes for a polypeptide(s) having a mass of 16,000-17,000 daltons. This polypeptide contains amino acid sequences corresponding to residues 11-18 and 19-25 of thymosin alpha 1. The yield of the octapeptide indicates that the 16,000-dalton peptide is the major product formed in the cell-free synthesis system containing the purified mRNA.